The conflictive relationship between satisfaction and income - Eduardo Lora; Juan Camilo Chaparro (Inter-American Development Bank, Research Department, 2008)
This paper makes use of the 2006 Gallup World Survey, which includes opinions on satisfaction with various aspects of life in 130 countries. Although a very solid relationship is found between satisfaction and income (both across and within countries), raising doubts regarding the well-known Easterlin Paradox, a new paradox arises: 'unhappy growth', where faster growth rates are accompanied by lower levels of satisfaction. The losses of satisfaction associated with growth are more pronounced in the material domains of life and are greater in richer and more urban societies. At the individual level, although higher incomes tend to be reflected in greater satisfaction, an increase in the income of the social group to which an individual belongs has the opposite effect. The conflictive relationship between satisfaction and income has implications for political economy. In particular, it suggests a simple mechanism for explaining various characteristic traits of economic and social populism.
Keywords: D63; E61; I31; O21; 330; Income; Quality of Life; GDP; Growth; Latin America